2018
DOI: 10.3389/fimmu.2018.02407
|View full text |Cite
|
Sign up to set email alerts
|

GDF15 Regulates Malat-1 Circular RNA and Inactivates NFκB Signaling Leading to Immune Tolerogenic DCs for Preventing Alloimmune Rejection in Heart Transplantation

Abstract: Recombinant human growth differentiation factor 15 (rhGDF15) affects dendritic cell (DC) maturation. However, whether GDF15 is expressed in DCs and its roles and signaling in DCs remain largely unknown. It is unclear whether GDF15-DCs can induce immune tolerance in heart transplantation (HT). This study aims to understand the impact of endogenous GDF15 on DC's development, function, underlying molecular mechanism including circular RNA (circRNA). This study will also explore GDF15-DC-mediated immune modulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 46 publications
2
67
0
Order By: Relevance
“…Inhibition of LFA-1 by GDF-15 would also impair the priming of antigen-specific T cells by dendritic cells. Such functional outcomes were independently observed in other studies (99,175). The latter study also found that a knockout of GDF-15 in immature dendritic cells promotes their maturation and enhances their immune stimulatory potential.…”
Section: Signaling Of Gdf-15 In the Tumor Microenvironmentsupporting
confidence: 74%
See 1 more Smart Citation
“…Inhibition of LFA-1 by GDF-15 would also impair the priming of antigen-specific T cells by dendritic cells. Such functional outcomes were independently observed in other studies (99,175). The latter study also found that a knockout of GDF-15 in immature dendritic cells promotes their maturation and enhances their immune stimulatory potential.…”
Section: Signaling Of Gdf-15 In the Tumor Microenvironmentsupporting
confidence: 74%
“…Transgenic expression of GDF-15 in dendritic cells, in contrast, induces immune-inhibitory molecules in dendritic cells which then enhance T cell exhaustion and promote the generation of regulatory T cells. Mechanistically, the observed GDF-15 mediated induction of a tolerogenic dendritic cell phenotype was found to depend on TGF-β receptors I and II (rather than on GFRAL), on repression of malate-1 circular RNA expression, on inhibition of NF-κB signaling, and on the induction of indoleamine-2,3-dioxygenase (IDO1) in dendritic cells (175). Effects of GDF-15 on LFA-1 were not investigated and possible problems resulting from the use of recombinant human GDF-15 (which may have contained TGF-β) were not discussed.…”
Section: Signaling Of Gdf-15 In the Tumor Microenvironmentmentioning
confidence: 98%
“…Besides the contribution of cholinergic receptors, we supposed the contribution of neurotrophic factors, axon-guidance proteins, and their respective receptors in neuron-MΦ interactions. GDF15 has been reported to suppress inflammatory responses in a murine model of endotoxin-induced sepsis and prevent maturation of inflammatory dendritic cells in a heart-transplantation model 91, 92 . Using an imiquimod- or IL-23-induced mouse model of psoriasis-like skin inflammation, GDF11 administration attenuated the severity of skin inflammation via suppression of the NF-κB signaling pathway 93 .…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of IL-27 is also correlated with the induction of IL-10 expressing CD4 + T cells ( 106 ). Moreover, DC transfected with MIC expression adenovirus could enhance T cell exhaustion and Treg proliferation and consequently promote the survival of cardiac allograft ( 100 , 107 ).…”
Section: The Function Of Tol-dcmentioning
confidence: 99%